Effect of Food Exports on Economic Growth: Fresh Insights from Italy - Othmani, Abdelhafidh; El Weriemmi, Malek; Bakari, Sayef (Universitas Airlangga, 2024)
This paper aims to explore the relationship between food exports and economic growth in Italy. To achieve this objective, we utilize annual data spanning from 1990 to 2021, employing cointegration analysis and the ARDL Model. The empirical findings reveal a positive impact of food exports on long-term economic growth. However, despite this positive correlation, our examination of stylized facts uncovers a downward trend in the share of food exports over the analysis period. While acknowledging the role of food exports as a contributor to economic growth, this underscores the need for the Italian authorities to acknowledge the sector’s significance and implement new economic policies and trade reforms to fortify this area of economic activity.